2016
DOI: 10.3389/fpls.2016.01789
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Rice OsLCB2a1 Gene and Functional Analysis of its Role in Insect Resistance

Abstract: In plants, sphingolipids, such as long-chain bases (LCBs), act as bioactive molecules in stress responses. Until now, it is still not clear if these lipids are involved in biotic stress responses to herbivore. Herein we report that a rice LCB gene, OsLCB2a1 encoding a subunit of serine palmitoyltransferase (SPT), a key enzyme responsible for the de novo biosynthesis of sphingolipids, plays a critical role in plant defense response to the brown planthopper (BPH) attack and that its up-regulation protects plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 68 publications
(83 reference statements)
1
6
0
Order By: Relevance
“…Overexpression of OsLCB2a in Arabidopsis led to the accumulation of LCB and ceramides compared with WT. These transgenic plants also displayed increased callose and wax deposition, an induction of SA-dependent and camalexin-dependent genes but a reduction of JA-related genes, and inhibited aphid infestation (Begum et al, 2016).…”
Section: Signalling Messengers In Biotic Stressmentioning
confidence: 93%
See 1 more Smart Citation
“…Overexpression of OsLCB2a in Arabidopsis led to the accumulation of LCB and ceramides compared with WT. These transgenic plants also displayed increased callose and wax deposition, an induction of SA-dependent and camalexin-dependent genes but a reduction of JA-related genes, and inhibited aphid infestation (Begum et al, 2016).…”
Section: Signalling Messengers In Biotic Stressmentioning
confidence: 93%
“…The role of sphingolipid metabolism in response to herbivory has been analysed (Begum et al, 2016). Overexpression of OsLCB2a in Arabidopsis led to the accumulation of LCB and ceramides compared with WT.…”
Section: Signalling Messengers In Biotic Stressmentioning
confidence: 99%
“…However, the fatty acid hydroxylase we identified does not appear to have high similarity to CER1 from cabbage or Arabidopsis. Regarding the palmitoyltransferase, overexpression of a rice gene, OsLCB2a1 , which encodes a subunit of a serine palmitoyltransferase, an enzyme important for sphingolipid biosynthesis, has been shown to result in higher wax deposition on leaves of transgenic Arabidopsis plants ( Begum et al, 2016 ). From our scans of the diploid genome, a gene (CUFF.9282.1) in the color QTL region on LG02 was found, which was annotated as very-long-chain 3-ketoacyl-CoA synthase (KCS) on the Genome Database for Vaccinium (GDV) website 3 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, the role of sphingolipids in the biotic stress response to herbivores is undefined. Recently, Begum et al (2016) reported that the OsLCB2a1 gene encoding a subunit of serine palmitoyltransferase (SPT) plays a critical role in the plant defense response to brown planthopper (BPH) attack and protected plants from herbivore infestation upon upregulation. Gene expression analysis in rice seedlings revealed the enhanced transcript levels of OsLCB2a1 gene at 4 h but decreased at 8-24 h after BPH attack.…”
Section: Sphingolipids In Plant-herbivore Interactionsmentioning
confidence: 99%
“…Sphingolipidomic analysis revealed elevated levels of trihydroxylated LCB, phytosphingosine, and phytoceramide by 1.7-and 1.3-fold, respectively. In addition, the reduced population size of the green peach aphid (Myzus persicae) was observed in transgenic Arabidopsis overexpressing OsLCB2a1 gene (Begum et al, 2016). Further investigation is needed to determine which signals were generated due to the overexpression of OsLCB2a1 gene in rice that protected the plants from brown planthopper infestation.…”
Section: Sphingolipids In Plant-herbivore Interactionsmentioning
confidence: 99%